Starting and Sustaining an Extracorporeal Membrane Oxygenation Program. Issue 1 (12th June 2022) - Dhar, Archana V.; Morrison, Tracy; Barbaro, Ryan P.; Buscher, Hergen; Conrad, Steven A.; Diaz, Rodrigo; Deng, Joseph; Ellis, W. Cory; Fortenberry, James; Heard, Micheal; Hyslop, Robert; Miranda, Dinis Reis; et al.
Abstract : The use of extracorporeal membrane oxygenation (ECMO) is growing rapidly in all patient populations, especially adults for both acute lung or heart failure. ECMO is a complex, high risk, resource-intense, expensive modality that requires appropriate planning, training, and management for successful outcomes. This article provides an optimal approach and the basic framework for initiating a new ECMO program, which can be tailored to meet local needs. Setting up a new ECMO program and sustaining it requires institutional commitment, physician champions, multidisciplinary team involvement, ongoing training, and education of the ECMO team personnel and a robust quality assurance program to minimize complications and improve outcomes.